Assessment of loss of 210Po from fish and shrimp by cooking and its effect on dose estimates to humans ingesting seafood. (September 2019) - Uddin, Saif; Behbehani, M.; Fowler, Scott W.; Al-Ghadban, Abdulnabi; Dupont, Sam
Abstract: An experimental study was conducted to assess loss of 210 Po due to cooking fresh seafood, and provide a more realistic and reliable dose estimate that humans may receive from consuming cooked seafood. Fresh fish and shrimp samples from Northern Gulf waters were grilled and boiled to simulate the effect of different cooking methods. Sixteen different species of fish were compared and significant differences in 210 Po concentration in uncooked samples were observed between species (ANOVA I, F15, 79  = 362.81, p < 0.0001). The effect of the treatment (uncooked, grilled, boiled and stock) was compared for each species and it was found that cooking led to a significant decrease in 210 Po concentration ranging from 14 to 58% compared to the uncooked samples, with no difference between grilled or boiled treatments. The effect of the cooking and shrimp treatment on 210 Po concentration was tested using ANOVA II after logarithmic transformation. Cooking led to a significant 38% reduction of 210 Po concentration as compared to uncooked treatments with no difference between grilled and boiled samples (ANOVA I: F3, 99  = 14.72, p < 0.0001). The two treatments with deveined shrimp led to a 75% decrease in 210 Po concentration as compared to all other treatments. As a consequence, cooked deveined shrimp contained an 84% lower 210 Po concentration than whole uncooked shrimp. As 210 Po is known to be the major contributor to radiation dose in humans consuming seafood, based on the results obtained, it is evident there is a need to re-examine how committed effective doses (CEDs) are best calculated for seafood consuming populations considering that most populations consume fish and shellfish cooked. Highlights: This is the first experimental assessment on loss of 210 Po in seafood from Kuwait. The Study provides a realistic assessment of dose to humans from cooked seafood. The seafood consumption in Kuwait varied between 35 and 203 g. The CED in Kuwait varies between 37 and 240 μSv.y-1 from seafood consumption.